Ice Shelf Basal Melt Rates in the Amundsen Sea at the End of the 21st Century. Issue 22 (16th November 2022) - Jourdain, Nicolas C.; Mathiot, Pierre; Burgard, Clara; Caillet, Justine; Kittel, Christoph
Abstract: Antarctic Ice Sheet projections show the highest sensitivity to increased basal melting in the Amundsen Sea. However, little is known about the processes that control future increase in melt rates. We build an ensemble of three ocean–sea‐ice–ice‐shelf simulations for both the recent decades and the late 21st century, constrained by regional atmosphere simulations and the multi‐model mean climate change of the fifth Climate Model Intercomparison Project under the RCP8.5 scenario. The ice‐shelf melt rates are typically multiplied by 1.4–2.2 from present day to future, for a total basal mass loss increased by 346 Gt yr −1 on average. This is equally explained by advection of warmer water from remote locations and regional changes in Ekman downwelling and in the ice‐shelf melt‐induced circulation, while increased iceberg melt plays no significant role. Our simulations suggest that high‐end melt projections previously used to constrain recent sea level projections may have been significantly overestimated. Plain Language Summary: Future sea level rise highly depends on how fast the ocean will melt the floating ice shelves in Antarctica, which modulates the ice flow from the ice sheet into the ocean. This is particularly true for the Amundsen Sea sector where the ice flow into the ocean is very sensitive to ocean‐induced melting. Here, we use a numerical model that represents the evolution of the Amundsen Sea, including under the floating ice shelves. Under a high‐end greenhouse‐gases concentration pathway, our simulations indicate that melt rates beneath the ice shelves may increase by 40%–120%. This is explained by both warmer seawater coming from distant regions and changes in the local wind stress. Our simulations suggest that high‐end melt projections previously used to constrain recent sea level projections may have been overestimated. Key Points: We present 1/12° ocean‐sea‐ice‐ice‐shelf projections at the end of the 21st century under the RCP8.5 scenario Ice shelf melt rates in the Amundsen Sea are typically multiplied by 1.4–2.2 from 1989–2009 to 2080–2100 Advection of warmer water from remote locations and reduced Ekman downwelling are the main drivers of changes in ice shelf melt rates